Annual report 2017: CGIAR Research Program on Fish - CGIAR Research Program on Fish (CGIAR Research Program on Fish, 2018)
The CGIAR Research Program on Fish Agri-Food Systems (FISH) is a new CRP that builds on earlier CRPs for Livestock and Fish (L&F) and Aquatic Agricultural Systems (AAS) as well as prior research by WorldFish and the managing partners. Key outcomes from the two flagships of Sustainable Aquaculture (FP1) and Sustaining Small-scale Fisheries (FP2) during 2017, including milestones achieved, are summarized below and in Tables A-1 and A-2.